PERANCANGAN SISTEM PNEUMATIK PLC TRAINER BERBASIS PEMOGRAMAN SOFTWARE FESTO FLUIDSIM 3.6 - Kamal Hamzah; Adhes Gamayel; Mohamad Zaenudin; Yasya Khalif Perdana Saleh; Nashrul Chanief Hidayat (Scientific Journal of Mechanical Engineering Kinematika, 2023)
This study aims to carry out pneumatic trainer motion simulations using Festo Fluidsim 3.6 software programming simulation. The trainer design has three main parts, namely a frame made of iron, a programmable automatic control device in the form of a PLC, and the third is a mechanical movement device in the form of a pneumatic circuit. This tool will be integrated into a circuit system, which is then tested with three experiments based on circuit simulations made in the Festo Fluidsim 3.6 software. The test results from 3 simulation experiments show that the PLC control system can send signals to the mechanical motion of a single-acting cylinder. The PLC control system can also send signals to the mechanical motion of a double-acting cylinder with non-simultaneous motion. Other than that, the PLC control system can send signals on the mechanical motion of a double-acting cylinder with simultaneous motion. The three experimental tests found that the number of strokes for a single-acting cylinder was more than that for a double-acting cylinder. The three tests showed that they could move the cylinder well with variations in flow control, namely the flow control openings of 25, 50, 75 and 100%.